2019
DOI: 10.1088/1361-6439/ab1da7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigations into microchannel formation in glass substrate using electrochemical discharge machining

Abstract: Microchannels formed in non-conductive substrates like fused silica, glass and quartz, etc, have wide applications in the field of micro-fluidic and lab-on-chip applications due to their optical transparency, chemical inertness, and biocompatible nature. Electrochemical discharge machining (ECDM) has emerged as a potential low-cost fabrication method to fabricate microfeatures in these materials, compared to conventional laser etching techniques. In this paper, numerical simulation and experimental fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Mishra et al [22] demonstrated numerical simulation and fabricated microchannels on the glass substrate. Machining voltage, pulse frequency and tool feed rate were considered as process parameters for analyzingsurface roughness (SR) and MRR of the microchannels as response parameters.…”
Section: Studies On Effect Of Electrical Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…Mishra et al [22] demonstrated numerical simulation and fabricated microchannels on the glass substrate. Machining voltage, pulse frequency and tool feed rate were considered as process parameters for analyzingsurface roughness (SR) and MRR of the microchannels as response parameters.…”
Section: Studies On Effect Of Electrical Parametersmentioning
confidence: 99%
“…Mishra et al [22]presented the trend for variation of MRR with tool feed rate asincreasing based on simulation and experimental results. For electro-chemical discharge drilling (ECDD) of silica glass, Rajput et al [17] reported that the tool feed rate was the most governingprocessparameter for controlling TWR based on RSM analysis.…”
Section: Studies On Miscellaneous Parametersmentioning
confidence: 99%
See 3 more Smart Citations